An integrated measurement system for analysing lower limb biomechanics during hockey skating - LeVangie, M.; Buckeridge, E.; Stetter, B.; Nigg, S.; Nigg, B. M. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Skating is the most fundamental skill in ice hockey at any level of play. However, due to the inherent difficulties of on ice data collection, little research has been conducted in this area. The complexity of on ice data collection has lead previous research to be conducted on smaller scales (Lafontaine, 2007), skating treadmills (Upjohn et al, 2008), or synthetic ice (Stidwell, 2009). To overcome these limitations, a novel, wireless, and portable measurement approach which integrates multiple data collection systems, was developed in order to compare on ice skating biomechanics between high and low caliber skaters. Methods: Nine high caliber and nine low caliber hockey players performed fifteen 30 m maximum effort forward skating trials. The 2nd and 6th strides were defined as acceleration (AC) and maximum velocity (MV) strides respectively. Independent measurement systems, housed in a backpack worn by the skater, were synchronized and collected through a remote laptop. A 3D accelerometer was mounted to the chassis of the right skate for the purpose of stride detection. Muscle activity of the vastus medialis (VM) and lateralis (VL), gluteus medius (GM), tibialis anterior (TA) and medial gastrocnemius (MG) was recorded using surface electromyography. Two biaxial goniometers were used to quantify the sagittal and frontal plane hip and knee joint angles. Biomechanical differences across caliber and strides were assessed using a mixed model ANOVA. Results: High caliber subjects exhibited an earlier onset and a greater peak muscle activity of the VL during MV strides compared to low caliber (p<0.01). They also demonstrated greater hip adduction at initial ice contact during AC and MV strides, and greater hip extension at toe-off during AC strides (p<0.01). Hip abduction velocity during AC and MV strides, and knee extension velocity during MV strides were also shown to be greater in high compared to low caliber subjects (p<0.01). Discussion: The integration of multiple measurement systems allowed for a successful data collection of lower limb biomechanics on ice. High caliber skaters demonstrated greater hip and knee angular velocities than low caliber skaters, coupled with earlier and higher peak knee extensor muscle activity. These caliber differences indicate that this measurements system is sufficiently sensitive to distinguish between the quality of players. As such, this system may be useful for athlete monitoring, and to provide coaches and athletes with biofeedback and training advice.